Causes of Wars and Their Role in Social Evolution: Generalization of Modern Concepts (Социология власти)
The article presents a systemic and historical view of wars taking into account the generalization of modern concepts about their nature and causes. The generalization is produced on the basis of a political and sociological apparatus with such basic concepts as: "concerns" of different types (including "interests", "motives", "goals", "values"), an extension of the challenge-response scheme (A. Toynbee), positive and negative "reinforcement" (Thorndike-Skinner), and "support structures" (A. Stinchcombe). All the concerns related to wars are based on the social universals of M. Weber and M. Mann: power-security, power-dominance, prestige-dignity-legitimacy, and wealth-resources-access to resources. Geopolitical concerns (regarding control over territories), symbolic stakes, and concerns with maintaining the international order are considered. The prioritization of relevant concerns changes in both the long run of social evolution and the short run of dynamics of interactions. The article considers spiral dynamics as a dynamic model of the cause of unintended wars "that no one wanted." Relevant decisions and actions of rulers and elites related to war are analyzed in the context of fast and slow thinking according to D. Kahneman. The general principles of social interaction and social evolution allow us to judge the conditions that increase and decrease the probability of new wars, as well as the regularities of the dynamics and termination of wars. Empirical generalizations of the characteristics of wars in world history made by modern specialists (S. Van Evera, G. Cashman, etc.) are discussed. It is shown what role wars play in the co-evolution of social, mental, and techno-natural orders, as well as in social evolution in general.